Can Analysis of Policy Decisions Spur Participation?. Issue 3 (16th May 2018) - Shapiro, Stuart
Abstract : Agencies are frequently required to analyze the impact of their decisions, particularly in the context of regulatory policy. Advocates of analysis have championed the transparency benefit of these requirements. But there has been very little attention paid to the effectiveness of analysis in spurring useful participation in practice. This article examines how analysis can hinder and motivate public participation. Interviews were conducted with 48 analysts (including economists, risk assessors, and environmental impact assessors). In addition I conducted a case study on a unique method for using analysis in partnership with participation, the use of panels of small business owners to evaluate a regulatory proposal by the Occupational Safety and Health Administration (OSHA). I find that participation in agency decisions as a result of traditional analytical requirements has been very uneven. Examples of success exist but so do cases where participation may be deterred by the density and complexity of analysis as well as cases of massive letter-writing campaigns ignored by decision-makers. I recommend a move toward simpler and earlier analysis, and the use of panels (such as described in the case study) to better take advantage of the potential synergy between analysis and participation.